Energy Management based on Supertwisting Sliding Mode in the Standalone Photovoltaic Power System with Battery Backup - Coteli, Resul; Caglayan, Ruhi Zafer; Kayisli, Korhan (ilhami Colak, 2024)
Electrical energy is an important issue of human being to perform our daily activities like food, transportation, heating, communications, leaving, and so on. Therefore, continues existence of electrical energy is a need of all human being. So that in stand-alone power system applications, energy storage is a very important issue. In these days, batteries are very popular energy storage equipment and controllability of the energy stored in the battery is very hot topic. In this article, the energy management in a stand-alone photovoltaic power system with battery backup is investigated. For this purpose, a simulation model based on Matlab/Simulink is built. Photovoltaic panel is operated to supply the maximum power by using perturb and observe maximum power point tracking (PO-MPPT) algorithm. The battery charging/discharging current is controlled via cascade control structure based on super twisting sliding mode controller. By appropriate control of the battery current, it is aimed to ensure the power balance among the photovoltaic panel, load and battery under different operating conditions as well as keep the DC bus voltage at the desired value. Simulation results show that the super twisting sliding mode controller successfully balances the power between the panel, load and battery and keeps DC bus voltage at reference value. © 2024, ilhami Colak. All rights reserved.
Keywords: Battery; Perturb and Observe Control; Photovoltaic; Super Twisting Sliding Mode Control